ANALISIS FUNGSI PELAYANAN KECAMATAN-KECAMATAN DI BAGIAN TIMUR KABUPATEN KONAWE SELATAN - Setiawan, Didi; Saenong, Zainuddin; Matoka, Ulfa (JURNAL EKONOMI UHO, 2016)
This research aims to: (1) identify and analyze the services functions of eastern of South Konawe Regency, (2) identify and analyze the degree of interaction between the district in eastern of South Konawe. Methods of collecting data is documentation of secondary data for 2015 period. The analyzed data used Schallogram and Gravity analysis. The results showed that the Ranomeeto district is in first hierarchy, besides that Konda district in the second. Konda and Moramo district have broader services and reach the three of the seven districts in the eastern of South Konawe as a result more populous and close distance.